Research Trends in Autism Spectrum Disorder: Evidence from Scopus-Indexed Bibliometric Data - Pelita Hayati; Tiwuk Herawati; Istiarsyah Istiarsyah; Siti Nurjannah; Yeni Irma Normawati (The Eastasouth Journal of Learning and Educations, 2026)
This study aims to analyze the intellectual structure and research trends in Autism Spectrum Disorder through a bibliometric approach based on Scopus-indexed publications. Data were retrieved using relevant keywords and filtered based on document type, language, and publication period to ensure quality and consistency. The analysis was conducted using VOSviewer to examine co-occurrence of keywords, co-authorship networks, and citation relationships. The results reveal a significant increase in ASD-related publications over time, indicating growing global research interest. The co-occurrence analysis identifies several dominant research clusters, including clinical and cognitive studies, early childhood diagnosis, genetic and biological mechanisms, and technology-based diagnostic approaches such as neuroimaging. The density visualization further confirms that core research themes are concentrated around clinical intervention and behavioral understanding, while emerging topics such as functional connectivity and advanced diagnostic imaging are gaining attention. Additionally, collaboration patterns show that research output is largely dominated by developed countries, suggesting the need for broader global participation. Despite the rapid development of the field, several gaps remain, particularly in underrepresented regions and longitudinal research designs. This study provides a comprehensive overview of the evolution of ASD research and offers insights into future directions, emphasizing the importance of interdisciplinary integration and technological innovation in advancing the field.